Síntese de 1,4-diazaciclo-2-ilidenos N-pirrolil/furanil substituídos - Mittersteiner, Mateus (2018)
This work presents the synthesis of piperazines, 1,4-diazepanes and 1,4-diazocanes pyrrolyl or furanyl-functionalized at the N4 position of the diazacycle. In this manner, four series of compounds were prepared, with a larger emphasis on seven-membered heterocycles (1,4- diazepanes), given the pronounced biological and pharmacological that this class of compounds usually present. The one-pot methodology developed for this work consists in the reaction of 5-bromo-1,1,1-trifluoro-4-methoxypent-3-en-2-one (enone) with terminal aliphatic diamines (1,2-diaminethane, 1,3-diaminepropane and 1,4-diaminebutane, in a molar ratio of 2:1), resulting in the addition of one molecule of diamine at the 4 position of two molecules of the enone. The dimer γ-bromo-β-aminovinyl trifluoromethyl ketone formed presented itself to be extremely reactive and the vinylic nitrogen being was able to attack the other CH2Br center. At this point, a second nitrogen nucleophile (aliphatic and aromatic amines) was added to promote the cyclocondensation reaction and prepare trifluoromethyl pyrroles connected directly at the 4 position of the heterocycle formed by the dimer. The final products were obtained with 40 – 71% overall yield. During the optimization of reaction conditions, it was observed the formation of a byproduct, that was identified as being the corresponding 1,4-diazacycle with a trifluoromethylated furan at N4 position (instead of the pyrrole), which is resulting of the cyclocondensation reaction of the enaminone in basic media. In this form, conditions for the synthesis of the compounds bearing a furan were investigated. Since the amine acted both as base and nucleophile in the preparation of the pyrroles derivatives, the reaction to prepare the furan was carried out using a non-nucleophilic base (Na2CO3) and the final compounds were obtained in 91 – 96% overall yields. The products obtained in this work were fully characterized by nuclear magnetic resonance of hydrogen and carbon 13, low-resolution mass spectrometry, elemental analysis, melting points and single crystal X-ray diffraction.